Improving Mathematical Problem Solving Ability Through Think Pair Share for Junior High School Students - Nanang; Rahmawati, Willy Aisyah Taufik (Universitas Pendidikan Ganesha, 2022)
In learning mathematics, problem-solving skills are very important. Problem-solving skills will help the person succeed in everyday life. This study aims to analyze the increase in mathematical problem-solving abilities (KPMM) of students whose learning uses the Think-Pair-Share (TPS) cooperative strategy. This research is a class action research that consists of three cycles. The subjects in this study were students of class VIII-A, consisting of 34 students. The instrument used is a mathematical problem-solving ability test (KPMM). Data analysis was carried out with an increased test (normalized gain), learning completeness, and the average level of mastery. Based on the KPMM test results, information was obtained that there were differences in classical learning mastery in aspects of mathematical problem-solving ability in cycles I, II, and III. These findings are supported by the number of students who complete each cycle. For KKM 65, in cycle I, the number of students who completed was 13 students (38.24% of 34 students). In cycle II the number of students who completed was 23 students (67.65% of 34 students), and in cycle III, the number of students who completed there was 28 students (82.35% of 34 students). It can be concluded that TPS learning using students working on worksheets in groups and being guided by the teacher on changing word problems into a mathematical model can increase the KPMM of students with high criteria. The number of students who complete cycle III is more than those who complete cycles I and II.